1996
DOI: 10.1111/j.1365-2389.1996.tb01851.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular enzyme activity in soil: effect of pH and ionic strength on the interaction with montmorillonite of two acid phosphatases secreted by the ectomycorrhizal fungus Hebeloma cylindrosporum

Abstract: The interaction of extracellular enzymes with the solid phase of the soil affects their mobility and their catalytic properties. In particular, adsorption on clay minerals is known to shift the optimum pH of the catalytic activity towards alkaline values. Two conflicting interpretations of this phenomenon have been proposed: a surface pH effect and a pH-dependent modification of the conformation of the adsorbed enzyme. To assess the two mechanisms, we studied the adsorption on montmorillonite of two extracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(76 citation statements)
references
References 40 publications
2
74
0
Order By: Relevance
“…3). These data are consistent with prior findings which indicate that soils and sediments bind nucleic acids (5,23), proteins (12), viruses (4), and presumably other cell-free biological macromolecules quite strongly.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…3). These data are consistent with prior findings which indicate that soils and sediments bind nucleic acids (5,23), proteins (12), viruses (4), and presumably other cell-free biological macromolecules quite strongly.…”
Section: Resultssupporting
confidence: 82%
“…The objective of this experiment was to demonstrate that the isotope values of samples obtained from bacterial injection experiments reflect transport of intact bacterial cells and not cell fragments or soluble cell components possibly released by the demise of added bacteria. To accomplish this, an intact-core experiment using SGW was performed to compare the breakthrough be- Since there is no a priori reason to expect differences in the behavior of cellular macromolecules synthesized using carbon in the form of 12 C, 13 C, or 14 C, provided that it is incorporated into bacterial cells in the same chemical form (in this case acetate) and under the same conditions, the 14 C isotope should function as a faithful analog of 13 C enrichment. For this experiment, a single culture of DA001 was grown on [ 14 C]acetate and then split into two equal aliquots, of which one was thoroughly lysed by sonication.…”
Section: Resultsmentioning
confidence: 99%
“…Although sorption on surfaces usually reduces enzyme activity, it also stabilizes the enzyme to the extent that much of the activity measured in soil enzyme assays may be due to stabilized enzymes (46). Sorption of an enzyme can also change its optimum pH by one or two pH units compared to that of the free enzyme in solution (31,40), with an increase in the optimum pH expected for enzymes sorbed on negatively charged surfaces, such as clays (26). For example, sorption on kaolinite increased the optimum pH of wheat acid phosphomonoesterase from 5.0 to 5.7 (40) and that of chitinase from 4.7 to 5.7 (48).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the sorption of an enzyme on a clay surface can increase its optimum pH by one or two pH units relative to that of the same enzyme in solution (31,40). This is due to "unfolding" of enzymes on solid surfaces, which is most likely to occur at soil pH values below the isoelectric point of the enzyme (26,38).…”
mentioning
confidence: 99%
“…Other studies have reported positive relationships between N deposition and PME activity (e.g., Phoenix et al 2003), although this was not found in our survey. PME activity is highly sensitive to differences in substrate pH above and below an optimum pH of 4.5 (Leprince and Quiquampoix 1996) and, in the present study, reduced N deposition significantly lowered soil pH (soil pH range in the survey 3.5-5.4), a phenomenon that has been observed in studies elsewhere (Stevens et al 2004;Power et al 2006). The influence of soil pH may, therefore, have confounded potential relationships between PME activity and N deposition.…”
Section: Overall Implications Of N Deposition Relationshipsmentioning
confidence: 54%